Inhibition of Rac1 activity by controlled release of NSC23766 from chitosan microspheres effectively ameliorates osteoarthritis development in vivo. Issue 1 (20th November 2013) - Zhu, Shouan; Lu, Ping; Liu, Huanhuan; Chen, Pengfei; Wu, Yan; Wang, Yanyan; Sun, Heng; Zhang, Xiaolei; Xia, Qingqing; Heng, Boon Chin; Zhou, Yiting; Ouyang, Hong Wei
Abstract : Background: Osteoarthritis (OA) is a degenerative joint disease characterised by cartilage degradation and chondrocyte hypertrophy. A recent study showed that Rac1 promoted expression of MMP13 and chondrocyte hypertrophy within the growth plate. These findings warrant further investigations on the roles of Rac1 in OA development and therapy in animal models. Objective: To investigate the role and mechanistic pathway of Rac1 involvement in pathological changes of OA chondrocytes in vitro and OA development in vivo, as well as to develop a strategy of modulating Rac1 activity for OA treatment. Material and methods: OA and normal cartilage from human or mice were used for immunohistochemical study and Rac1 activity assay. Chondrocytes treated with IL1β and the untreated control were subjected to the Rac1 activity assay. Chondrocytes transfected with CA-Rac1, DN-Rac1 or GFP were cultured under conditions for inducing calcification. To evaluate the effect of Rac1 in OA development, an OA model was created by anterior cruciate ligament transection in mice. CA-Rac1, DN-Rac1 and GFP lentivirus, or NSC23766, were injected intra-articularly. Joints were subjected to histological analysis. Results: It was found that there is aberrant Rac1 activation in human OA cartilage. Rac1 activity could also be elevated by IL1β. Additionally, activated Rac1 promoted expression of MMP13, ADAMTS-5 and COLX by chondrocytes, partially through the β-catenin pathway. Moreover, activation of Rac1 in knee joints by CA-Rac1 lentivirus accelerated OA progression, while inhibition of Rac1 activity by DN-Rac1 lentivirus or Rac1 inhibitor NSC23766 delayed OA development. Therefore, we developed a strategy of controlled release of NSC23766 from chitosan microspheres to OA joints, which effectively protected cartilage from destruction. Conclusions: These findings demonstrated that Rac1 activity is implicated in OA development. Also, controlled release of Rac1 inhibitor is a promising strategy for OA treatment.